P(3,7) Q(11,-6)

We have the point R on the y-axis,

==> R (0,y)

Such that:

PR = QR

PR= sqrt[(3-0)^2 + (7-y)^2]

QR= sqrt[(11-0)^2 + (-6-y)^2

==> sqrt[(9+(7-y)^2]= sqrt[121 + (-6-y)^2]

Square both sides:

==> 9+ (7-y)^2 = 121 + (-6-y)^2

Open brackets:

==> 9 + 49 -14y + y^2...

## Unlock

This Answer NowStart your **48-hour free trial** to unlock this answer and thousands more. Enjoy eNotes ad-free and cancel anytime.

Already a member? Log in here.

P(3,7) Q(11,-6)

We have the point R on the y-axis,

==> R (0,y)

Such that:

PR = QR

PR= sqrt[(3-0)^2 + (7-y)^2]

QR= sqrt[(11-0)^2 + (-6-y)^2

==> sqrt[(9+(7-y)^2]= sqrt[121 + (-6-y)^2]

Square both sides:

==> 9+ (7-y)^2 = 121 + (-6-y)^2

Open brackets:

==> 9 + 49 -14y + y^2 = 121+36 +12y + y^2

==> 58 -14y = 157 + 12y

==> 26y = -99

==> y= -99/26

==> R (0, -99/26)